2021
DOI: 10.1080/23802359.2021.1955635
|View full text |Cite
|
Sign up to set email alerts
|

Complete mitochondrial genomes of two damselfly species in coenagrionidae and phylogenetic implications

Abstract: Agriocnemis femina (Brauer, 1868) and Ischnura senegalensis (Rambur, 1842) are two damselflies inhabiting paddy lands. As an intermediate predator, they play an important role in controlling certain crop pest and mosquitoes. In this study, we sequenced complete mitogenomes of these two species. The total length of mitogenomes is 15,936 bp in A. femina and 15,762 bp in I. senegalensis. Both of mitogenomes consist of 13 protein-coding genes, 22 tRNA genes, two rRNA genes, and one control region. The close relat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…The phylogenetic relationship of Euphaeidae obtained from the analyses is also consistent with other previous studies, where Euphaeidae is phylogenetically closer to the family Pseudolestidae (Jiang et al. 2021 ; Wang et al. 2021 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The phylogenetic relationship of Euphaeidae obtained from the analyses is also consistent with other previous studies, where Euphaeidae is phylogenetically closer to the family Pseudolestidae (Jiang et al. 2021 ; Wang et al. 2021 ).…”
Section: Discussionsupporting
confidence: 90%
“… 2016 ; Jiang et al. 2021 ). Odonates are also excellent health indicators of aquatic ecosystems and are well-distributed in tropical and subtropical regions (Chee Yen and Mohamed Dawood, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The cultivation of rice might be a key factor in promoting gene exchanges among those populations. I. senegalensis is a common species found in rice fields (Hendawy et al, 2005; Jiang et al, 2021; Kandibane et al, 2005). India, South East Asian, and East Asia are the major rice cultivating areas in the world (Chandio et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Large areas of rice fields provide a suitable ecosystem for the breeding and dispersing of I. senegalensis (Pavithran, Chitra, and Ramanathan, 2020; Sugita et al, 2018). Investigations suggested that only several damselfly species were widely distributed in rice fields, including I. senegalensis (Jiang et al, 2021; Pavithran, Chitra, Arulprakash, and Sugumaran, 2020; Wakhid et al, 2020). During the season of rice cultivation, I. senegalensis could expand their population via large area of rice fields.…”
Section: Discussionmentioning
confidence: 99%